Poškodbe drevja zaradi abiotskih naravnih motenj na bukovih rastiščih v Sloveniji s poudarkom na snegolomih - Klinar, Blanka (Acta silvae et ligni, 2020)
We studied snow damage to individual trees in beech stands in Slovenia. The analysis included 22,609 compartments with at least 10 % of European beech (Fagus sylvatica) in the total growing stock. In salvage harvesting due to snow and wind damage, conifers represented a higher proportion than deciduous species, yet their proportions were similar after ice damage. Mainly younger and middle-aged trees of 20%40 cm in dbh were damaged by heavy snow load. On a sample of 363 compartments, for which data on daily snow precipitation were obtained, a binary logistic regression model to predict the probability of snow damage occurrence was developed. The sum of snow cover in spring months, phytogeographical region, rockiness, slope inclination, and bedrock were statistically significant predictors; the key predictor was the sum of snow cover in spring months. The relatively high salvage felling in forests on beech sites can partly be explained by alterations in forests due to the admixture of Norway spruce (Picea abies), since beech is less susceptible to snow damage compared to spruce. To improve stand resistance, classical thinnings from above should be frequent and of lower intensity, or alternative types of crop tree situational thinning should be applied in younger and middle-aged even-aged stands.
Keywords: binarna logistična regresija; binary logistic regression; bukova rastišča; damage occurrence; European beech sites; Fagus sylvatica; forest; gozdovi; naravne motnje; natural disturbance; pojav poškodbe; snegolomi; snow